Kebijakan Politik Kerukunan Antaragama di Indonesia Era Reformasi - Jamaluddin, Jamaluddin (Al-Riwayah : Jurnal Kependidikan, 2017)
Indonesian reformation era begins with the fall of President Suharto. Political transition and democratic transition impact in the religious life. Therefore, understandably, when the politic transition is not yet fully reflects the idealized conditions. In addition to the old paradigm that is still attached to the brain of policy makers, various policies to mirror the complexity of stuttering ruler to answer the challenges of religious life. This challenge cannot be separated from the hegemonic legacy of the past, including the politicization of SARA. Hegemony that took place during the New Order period, adversely affected the subsequent transition period. It seems among other things, with airings various conflicts nuances SARA previously muted, forced repressive. SARA issues arise as a result of the narrowing of the accommodation space of the nation state during the New Order regime. The New Order regime has reduced the definition of nation-states is only part of a group of people loyal to the government to deny the diversity of socio-cultural reality in it. To handle the inheritance, every regime in the reform era responds with a pattern and a different approach. It must be realized, that the post-reform era, Indonesia has had four changes of government. The leaders of every regime in the reform era have a different background and thus also have a vision that is different in treating the problem of racial intolerance, particularly against religious aspect. This treatment causes the accomplishment difference each different regimes of dealing with the diversity of race, religion and class that has become the hallmark of Indonesian society.